Stability of potassium-promoted hydrotalcites for CO2 capture over numerous repetitive adsorption and desorption cycles - Xin, Kun; Boon, Jurriaan; van Dijk, H. A. J.; van Sint Annaland, Martin (Frontiers in Chemical Engineering, 2024)
Hydrotalcite-based adsorbents have demonstrated their potential for CO 2 capture, particularly in the sorption-enhanced water-gas shift (SEWGS) process. This study aims to investigate the long-term stability of a potassium-promoted hydrotalcite-based adsorbent (KMG30) over many repetitive cycles under various operating conditions. The stability of the adsorbent, both in terms of its structure and sorption capacity, is examined through multiple consecutive adsorption and desorption cycles. However, it is observed that the capacity for CO 2 adsorption decreases when subjected to many repeated cycles of CO 2 adsorption followed by N 2 flushing, or to many repeated cycles of H 2 O adsorption followed by N 2 flushing. In-depth investigations employing various techniques such as thermogravimetric experiments, XRD, BET, and SEM-EDX analyses were conducted to elucidate the underlying phenomena that can explain this observed behavior. The former can be attributed to aggregation of K 2 CO 3 from the sorbent during the CO 2 adsorption and N 2 flushing cycles (which can be reversed by re-dispersing the K 2 CO 3 either by exposure to air or by processing the sorbent with cycles of CO 2 /H 2 O adsorption followed by N 2 flushing), whereas the latter is ascribed to the only partial regeneration of the reactive site (referred to site C in earlier work), most likely associated with K 2 CO 3 modification on MG30. In this case, morphological changes were found to be insignificant. Remarkable stability of KMG30, as known from SEWGS process studies, was confirmed during cycles of CO 2 adsorption/steam purge. These findings significantly enhance our understanding of the stability of potassium-promoted hydrotalcite-based adsorbents and provide valuable insights for the design of diverse sorption processes.